Analisis Dan Perancangan Marketplace Berbasis Mobile Dengan Metode E-Marketing Sostac (Kasus Laundry Mobile App) - Aditya, Muhammad Haycal; Edi, Sri Winarso (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2025)
Laundry businesses provide services related to washing clothes and similar items. In terms of marketing, they still rely on promotions through various social media platforms such as Facebook, WhatsApp, Instagram, and others. Social media enables them to promote their services to a broader audience. However, while this strategy is quite effective in certain social circles, promotions through Facebook and similar platforms are often easily forgotten. This is because most users utilize social media to interact with family members or discuss current issues, rather than searching for services like laundry. Additionally, there is a lack of clear information about the service packages offered, which makes it difficult for potential customers to understand the available options. Another challenge faced is the limited ordering system, where customers can only place orders by phone or by visiting the business location. Currently, promotions are also confined to a limited network, such as coworkers and relatives. Therefore, there is a need for efforts to expand the promotional reach so that this laundry business can attract more customers. This study uses the SDLC software development method, implemented in the form of a mobile application with the e-marketing SOSTAC approach. It is hoped that this new system will enable the laundry business to market its services more widely, increase its appeal to new customers, and streamline the generation of reports needed for business operations.